P1557EFFECTIVENESS OF INTERVENTION FOR SAFETY CONFIRMATION OF HEMODIALYSIS PREPARATION PROCESS. (6th June 2020) - Higashitsuji, Yasunori; Tobita, Itoko; Kano, Takashi; Shima, Kumiko; Sasaki, Masako; Ogawa, Masako
Abstract: Background and Aims: It has been determined that more than half of the medical errors related to haemodialysis treatment are due to the preparation process at the initial stage of treatment, and that the errors are mainly caused by insufficient confirmation behaviour of healthcare professionals. Pointing confirmation and double check have been proven effective as safety treatments, but no specific strategy has been established to verify these insufficient confirmation behaviours. This study clarified the actual behaviour of healthcare professionals engaged in haemodialysis during the preparation process at the initial stage of treatment and defined the confirmation behaviour necessary to start safe haemodialysis based on the results. Moreover, the aim was to assess the effectiveness of an intervention program for enhancing adherence to confirmation practice. Method: A first study was conducted to investigate the actual state of behaviour, and a second study to verify the effectiveness of an intervention program. In the first study, we monitored and analysed the actual behaviours of 23 clinical engineering technicians and 14 registered nurses at a dialysis centre during the preparation process (218 steps) at the initial stage of treatment, and calculated their adherence rates. In the second study, the final confirmation process at the initial stage of treatment was determined (13 steps), and an intervention program aimed at adherence was devised. To verify its effectiveness, 18 clinical engineering technicians and 8 registered nurses were randomly divided into an experimental group (E) and a control group (C). The intervention program for Group E comprised baseline without intervention, intervention 1 (verbal explanation of confirmatory behaviour), intervention 2 (adding graphic feedback), intervention 3 (adding video feedback), and follow-up without intervention. That of Group C comprised only baseline and intervention 1. The adherence rate to the final confirmation process in both groups was calculated. Results: In the first study, the adherence rate to the preparation process at the initial stage of treatment was 67.2%, and the adherence rate in the confirmation process immediately after the start of dialysis was 21.0%, which was remarkably low. In the second study, the adherence rate to the final confirmation process in Group E was 17.1% at baseline, 45.5% after intervention 1, 65.5% after intervention 2, 90.4% after intervention 3, and 93.9% at follow-up. In contrast, the adherence rate in Group C was 8.6% at baseline and 50.4% after intervention 1. Conclusion: The adherence rate to the preparation process at the initial stage of treatment was less than 70%. Furthermore, the intervention program using graphic feedback and video feedback increased the adherence rate to the final confirmation process. Intervention programs aimed at the behaviour modification of healthcare professionals involved in haemodialysis have increased the adherence rate to confirmation actions in the final confirmation step of haemodialysis, and it has become clear that verbal teaching and visualized feedback are effective.